38. ASSESSMENT OF CUSTOMERS SATISFACTION AND SOME RELATED FACTORS AT THE NUTRITIONAL COUNSELING DEPARTMENTS AT THE INSTITUTE OF NUTRITION, 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe customers satisfaction with nutritional counseling services at the Nutrition Institute in 2023.Subject and method: A descriptive cross-sectional survey was conducted, gathering quantitative data from 270 clients receiving nutritional counseling services. Surveys were administered based on Decision 3869/QĐ-BYT issued on August 28, 2019, by the Ministry of Health.Results: The average satisfaction score among clients was 4.54 ± 0.43, with an overall satisfaction rate of 87.8%. The highest satisfaction rate was observed in "Healthcare staff's attitude and skills," at 97.4%, scoring 4.76 ± 0.43. The lowest satisfaction rate was in "transparency of information and administrative procedures," at 80.7%, scoring 4.41 ± 0.48. There was a statistically significant difference in satisfaction levels between urban and rural areas (p < 0.05).Conclusion: It is essential to invest in and improve the factors with lower satisfaction ratings to enhance service quality and attract more regular customers to the nutritional consultation services at the National Institute of Nutrition.
Keywords: Satisfaction; Customers; Institute of Nutrition